PETA KOMPETENSI PROFESIONAL GURU TEKNIK KOMPUTER DAN JARINGAN SEKOLAH MENENGAH KEJURUAN NEGERI KABUPATEN CILACAP - Junedi Haryanto; Edy Susatya; Muhammad Kunta Biddinika (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2021)
The research objective was to analyze the educational background of Computer and Network Engineering (TKJ) teachers at SMK Negeri Cilacap Regency, describe what elements or insights are contained in TKJ teacher competency standards (SKG), and map the professional competence of TKJ teachers based on teacher competency standards at State Vocational High Schools. Cilacap Regency. The research method is quantitative research with a descriptive research design. The place of research is SMK Negeri in Cilacap Regency with the subject of research is the teachers of SMK Negeri 1 Cilacap and SMK Negeri 1 Binangun, the data collection technique uses questionnaires and the data analysis technique uses descriptive quantitative statistics. The results showed that; (1) the educational background of TKJ teachers at SMK Negeri Cilacap Regency is in accordance with government regulations regarding the number of teachers and the number of study groups and according to the field of expertise of educator certificates, (2) the elements contained in the SKG are planning, assembling and installing computers, building a digital information network, and building a data network system and (3) a map of the professional competency of TKJ teachers, the average teacher mastery of professional competence is 76% in the very good category, there are some teachers in the master category in the percentage range of 55% to 71%..